1993
DOI: 10.1161/01.str.24.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar infarction. Clinical and anatomic observations in 66 cases.

Abstract: Background and Purpose: Cerebellar infarction displays diflerent clinical features, depending on the vascular territory involved. We studied patients with infarcts in the territories of the posterior inferior cerebellar artery or the superior cerebellar artery to compare their clinical presentation, course, and prognosis.Methods: We retrospectively analyzed the clinical features, laboratory data, and imaging studies of 66 patients with cerebellar infarction collected consecutively at five institutions. All the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
159
6
11

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(185 citation statements)
references
References 30 publications
(6 reference statements)
9
159
6
11
Order By: Relevance
“…In a population-based study involving patients presenting to emergency departments with dizziness that was not focused specifically on acute vestibular syndrome, patients with unsteadiness as part of their symptom complex were at a slightly increased risk of stroke, but the presence of vertigo versus other types of dizziness was found to predict stroke with equal likelihood. 15 These results support those of disease-based studies (reviewed elsewhere 37 ) that indicated that type of dizziness was inconsistently described by patients with disorders known to cause acute vestibular syndrome such as vestibular neuritis, 77 stroke in the posterior fossa 47,52 and cerebellar hemorrhage. *Only the three studies identified in the systematic review that reported the frequency of underlying causes and used an adequate (medium-quality) or superior (high-quality) reference standard to rule stroke in or out were considered for this table (criteria used to assess strength of reference standards are defined in Appendix 1).…”
Section: Typesupporting
confidence: 70%
“…In a population-based study involving patients presenting to emergency departments with dizziness that was not focused specifically on acute vestibular syndrome, patients with unsteadiness as part of their symptom complex were at a slightly increased risk of stroke, but the presence of vertigo versus other types of dizziness was found to predict stroke with equal likelihood. 15 These results support those of disease-based studies (reviewed elsewhere 37 ) that indicated that type of dizziness was inconsistently described by patients with disorders known to cause acute vestibular syndrome such as vestibular neuritis, 77 stroke in the posterior fossa 47,52 and cerebellar hemorrhage. *Only the three studies identified in the systematic review that reported the frequency of underlying causes and used an adequate (medium-quality) or superior (high-quality) reference standard to rule stroke in or out were considered for this table (criteria used to assess strength of reference standards are defined in Appendix 1).…”
Section: Typesupporting
confidence: 70%
“…A decompressive posterior fossa craniotomy should be emergently performed if the patient does not improve immediately. 14,15 Our patient was managed conservatively entirely in close liaison with the neurosurgeons. Physiotherapy was instituted and patient discharged in good condition after a six weeks period of hospital stay on anti-hypertensives.…”
mentioning
confidence: 85%
“…The occlusion of the SCA, albeit rare, produces a characteristic clinical picture that results from the infarction of the superior cerebellar cortex, the dentate nucleus and sensory tracts located in the tegmentum of the rostral pons [6,17,19]. Patients with an injury of the SCA have dysarthria, which may be associated with mild ataxia, ipsilateral dissymmetry, and axial lateropulsion [2,10,11].…”
Section: Discussionmentioning
confidence: 99%